Problems of industrial arts instruction in the Division of Cagayan I - De Yro, Tomas Baluyan 1920- (s.n.], 1969)
This study determined the problems of industrial arts instruction in the Division of Cagayan I using the normative-survey method. This study aims to bring out whatever existing strengths and weaknesses of the program. The author hopes that the findings would be useful in the planning of an in-service training in industrial arts for administrators and teachers of the Division.